Development Of Hedging Strategy For Exporters And Importers Succoured By Multi-Criteria Decision-Making Techniques (AHP And WASPA) - et. al., S.Iswarya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hedging strategy decision for a firm is very challenging as it impacts the financials of the firm in multiple facets. This study aims to solve the real time problem by finding the criteria weights for various hedge influencing factors and ranking the best one using MCDM techniques like Analytic Hierarchal Process (AHP) and Weighted Aggregated Sum Product Assessment (WASPA) method. Snowball sampling technique was executed considering the sensitivity of the data. The respondents were finance executives and managers who play a crucial role in hedging decisions in their organisations and who are highly experienced in this domain. The total number of respondents were 83 and they belonged to firms which perform both import and export business activity. The findings reveal that, exposure coverage and firms policy decision influence 49 % of criteria weight. The best solution for hedging strategy would be the firm should equally be involved in both internal and currency derivative to mitigate the exposure, followed by currency derivatives methods and internal hedging strategy.